1994
DOI: 10.1192/bjp.165.3.347
|View full text |Cite
|
Sign up to set email alerts
|

The Nithsdale Schizophrenia Surveys

Abstract: Schizophrenic patients saw their parents as showing much less warmth, and the severity of currents symptoms was associated with perceived parental rearing attitudes. The hostility component of high expressed emotion may be a parental trait which exists before the illness begins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As the authors point out 'MZ twins are genetically identical and any differences between such twins are due to non-genetic causes' (ibid., p. 67). The Scottish study, moreover, found no significant relationship between 'premorbid personality and social adjustment' (as assessed by the patients' mothers), and parental rearing styles (McCreadie, Williamson, Athawes, Connolly, & Tilak-Singh, 1994). Also, when we consider the relationship between early trauma and attachment disorganization, meta-analytic evidence shows that disorganized infant attachment does not arise through temperamental (van Ijzendoorn, or genetic variables (Bokhorst, Bakermans-Kranenburg, Fearon, van Ijzendoorn, Fonagy, & Schuengel, 2003;Bakermans-Kranenburg & van Ijzendoorn, 2004).…”
Section: Distorted Memory: the Negative Bias Hypothesismentioning
confidence: 90%
See 3 more Smart Citations
“…As the authors point out 'MZ twins are genetically identical and any differences between such twins are due to non-genetic causes' (ibid., p. 67). The Scottish study, moreover, found no significant relationship between 'premorbid personality and social adjustment' (as assessed by the patients' mothers), and parental rearing styles (McCreadie, Williamson, Athawes, Connolly, & Tilak-Singh, 1994). Also, when we consider the relationship between early trauma and attachment disorganization, meta-analytic evidence shows that disorganized infant attachment does not arise through temperamental (van Ijzendoorn, or genetic variables (Bokhorst, Bakermans-Kranenburg, Fearon, van Ijzendoorn, Fonagy, & Schuengel, 2003;Bakermans-Kranenburg & van Ijzendoorn, 2004).…”
Section: Distorted Memory: the Negative Bias Hypothesismentioning
confidence: 90%
“…In one study, of seventy-two people diagnosed with 'schizophrenia', those who experienced one or both parents as low care and high over-protection had an earlier age of first hospitalization and were more likely to be readmitted (Parker, Fairley, Greenwood, Jurd, & Silove, 1982). Other studies have not found any relationship between perceived parental rearing styles and age of onset (Warner & Atkinson, 1988;McCreadie, Williamson, Athawes, Connolly, & Tilak-Singh, 1994). However, it has been found that patients who scored their parents positively on the PBI 'tended to experience a milder course of illness if they were in frequent contact with them, and a more severe course if they were not' (Warner & Atkinson, 1988, p. 344).…”
Section: Onset and Remissionmentioning
confidence: 99%
See 2 more Smart Citations